Liver abscess caused by multidrug-resistant pathogen Stenotrophomonas maltophilia: A rare case report - Uneza Husain; Vivek Gupta (Journal of Family Medicine and Primary Care)
Intra-abdominal infections are often implicated in the causation of liver abscesses, and the transmission occurs via the vascular route. We report a rare case of abscess of the liver, Stenotrophomonas maltophilia being the etiological agent, in a 25-year-old female residing in Lucknow, India. S. maltophilia is a common nosocomial pathogen responsible for causing pneumonia, bacteremia, meningitis, endocarditis, gastrointestinal, ocular, skin, soft tissue, bone, joint, urinary tract infections, and even septic shock, especially in intensive care units. However, very few case reports are from India and globally, highlighting it as a pathogen in a liver abscess case. Hence this study is relevant in the context of providing case details that can help clinicians and microbiologists to suspect and diagnose more such cases that might be missing in history.